Crime and Persistent Punishment : A Long-Run Perspective on the Links between Violence and Chronic Poverty in Mexico - Martinez-Cruz, Adan L. (World Bank, Washington, DC, 2016)
The relationship between violence and chronic poverty has been studied mostly in the context of war or long-term episodes of conflict. In contrast to previous studies, this paper explores whether violence that does not include the shattering of infrastructure impacts the chance that poverty may remain chronic. A long-run perspective is gained by analyzing unique, recently gathered panel data at the municipality level in the Mexican context, covering the period from 1990 to 2010. Violence is measured as the number of non-drug-related homicides per 100,000 inhabitants. A municipality is classified as chronically poor if the percentage of people in food poverty remains above the national average during two consecutive periods. Econometric analysis is carried out through discrete choice models. Putting the results in context, consider of a chronically poor municipality in 2005 in which average household income is below the 25th percentile in 2000. If this municipality had a 10.47 non-drug-related homicide rate, the 75th percentile in 2000, its chance of remaining chronically poor into 2005 was almost double the corresponding chance of a municipality with the same mean household income but at the national median of violence in 2000 (zero non-drug-related homicides).